Spatiotemporal analysis of pulmonary tuberculosis in the central region of the Zhejiang Province, China (2016–2024) - Kaixuan Zhang; Zuokai Yang; Jiamei Sun; Kui Liu; Qiaoling Lu (Frontiers in Public Health)
BackgroundIn recent years, Shaoxing City, located in central Zhejiang Province, has experienced a slow decline in the incidence of pulmonary tuberculosis (PTB). Therefore, there is an urgent need to elucidate the potential causes for this decline through spatiotemporal analyses to provide a scientific basis for targeted prevention and control. We aimed to explore the spatiotemporal distribution of PTB notification rates in Shaoxing City from 2016 to 2024 and identify high-incidence clusters, thereby offering data-driven insights to optimize regional PTB control strategies.MethodsStatistical analyses were conducted using R and Excel on all reported active PTB cases in Shaoxing City. Spatiotemporal analysis of case distribution and regional clustering was conducted using ArcGIS and SatScan.Results and discussionIn total, 17,298 active PTB cases were registered between 2016 and 2024, including 9,749 laboratory-confirmed and 7,549 clinically diagnosed cases. The male-to-female ratio was 2.34:1. Farmers represented 68.2% of all cases. The PTB notification incidence showed a gradual decline. Spatial autocorrelation results revealed 52 sub-districts with high-high clusters over the nine-year period, primarily in Shengzhou and Xinchang counties. Spatiotemporal scan analysis identified one primary cluster area (RR = 1.62, LLR = 170.87, p < 0.001) and two secondary clusters between 2016 and 2024. The incidence of PTB in Shaoxing City showed a downward trend, though the decline was relatively slow. The southeastern region should be prioritized in efforts to accelerate the End TB Strategy. Overall, comprehensive and intensive interventions, such as large-scale chest X-ray screening and health education programs, should be enhanced to effectively curb PTB transmission, especially among males and farmers.